Ecofriendly and low-cost sample preparation methods for magnesium determination in beer - Lisboa, Thalles Pedrosa; Lemos, Luiza Conforte da Silva; Calzavara, Fillipe Caitano; Barbosa, Beatriz Silva; Baia, Gabriela Ezura; de Farias, Davi Marques; de Faria, Lucas Vinicius; Matos, Maria Auxiliadora Costa; da Silva, Júlio César José; de Oliveira, Marcone Augusto Leal (Eclética Química, 2021)
Ultrasound-assisted extraction and direct analysis were compared with total digestion for magnesium determination in beer samples by flame atomic absorption spectrometry. The method for total digestion used concentrated nitric acid under plate heating. In optimized instrumental conditions, validation of the analytical method was promoted, with good linear range (0.06 to 0.5 mg L–1), low limits of detection and quantification (0.04 and 0.12 µg g–1, respectively), good precision, relative standard deviation (RSD) < 3.4%, and accuracy (recovery levels of 91.5 to 99.0%). The characteristic concentration (C0) was 9 µg L–1. The extraction procedure was performed in a 1:1 nitric acid solution for 55 min in an ultrasonic bath at 60 °C, while the direct analysis involved a dilution of the samples in a 2% v/v nitric acid solution. The different sample preparation methods were applied to 13 beer samples and at a 95% confidence level, no significant differences were observed. Thus, direct analysis proved to be more suitable for quality control routines of beer samples in the industry.